Epidemiology and survival of non-malignant and malignant meningiomas in middle-aged females, 2004-2018 - Cao, Junguo; Yan, Weijia; Hong, Xinyu; Yan, Hong (Frontiers in oncology, 2023)
Background: The incidence of meningioma is disparate to sex: meningiomas are more common in women than in men, especially in middle-aged women. Understanding the epidemiology and survival of middle-aged women with meningiomas would help estimate their public health impacts and optimize risk stratification. Methods: Data on middle-aged (35-54 years) female patients with meningiomas between 2004 and 2018 were obtained from the SEER database. Age-adjusted incidence rates per 100 000 population-years were calculated. Kaplan-Meier and multivariate Cox proportional hazard models were utilized in the overall survival (OS) analysis. Results: Data from 18302 female patients with meningioma were analyzed. The distribution of patients increased with age. Most patients were White and non-Hispanic, according to race and ethnicity, respectively. Over the past 15 years, non-malignant meningiomas have shown an increasing trend; however, malignant meningiomas have shown an opposite trend. Older age, Black population, and large non-malignant meningiomas tend to have worse prognoses. Surgical resection improves OS, and the extent of resection is a critical prognostic factor. Conclusions: This study observed an increase in non-malignant meningiomas and a decrease in the incidence of malignant meningiomas in middle-aged females. The prognosis deteriorated with age, in Black people, and with large tumor size. Additionally, the extent of tumor excision was found to be a significant prognostic factor.
Gesehen am 20.06.2023